Implementasi Association Rule Mining Untuk Menentukan Menu Paket Makanan Dengan Algoritma FIN Menggunakan Nodesets (Studi Kasus R.M. Lesehan Nova Sragen) - Riski Nova Saputra; Muhammad Tanzil Furqon; Indriati Indriati (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Restaurant of Lesehan Nova Sragen has a variety of menu items are quite a lot of 116 food menu items and 44 drink menu items. Due to the high variations of menu items makes consumers take longer to select order menu items. Author provides solutions to restaurant's owner to create a menu package based on consumer history in selecting menu items. So as to improve restaurant service to consumers. To create package menu author using FIN algorithm. Fin algorithm is used to perform mining frequent itemset to sales transaction data. Fin algorithm is implemented on automatic package menu builder system. Based on test results, minimum value of support = 11 has resulted in proportional package menu variation ,and has been representative with consumer choice. Variation number of resulting package menu is 6 variations of package menu.